E-164 Recurrent strokes as the initial presentation of colorectal adenocarcinoma. (23rd July 2022) - Babici, D; Phillip Johansen, P; Rodriguez-Hernandez, A; Sommerville, S; Snelling, B; Miller, TD
Abstract : Introduction: The relationship between thromboembolism and cancer was first described by Trousseau in 1865, who discovered the incidence of thromboembolic events in patients with cancer to be 15% in clinical findings and up to 50% in post-mortem studies. The hypercoagulable state in patients with cancer, because of endothelial damage and vascular compression or infiltration, is responsible for the formation of thrombi which may lead to ischemic strokes. In contrast, marantic endocarditis (non-bacterial thrombotic endocarditis, or NBTE), arterial tumor emboli, and septic emboli are common causes of embolic strokes in cancer patients. Methods: Single case study Case Description: The authors present the case of a patient with no past medical history who presented with multiple cranial nerve deficits of the right trigeminal, facial, and hypoglossal nerves. MRI of the brain revealed a mass in Meckel's cave, which explained the involvement of the trigeminal nerve (CN V), but not the facial (CN VII) and hypoglossal (CN XII) nerves. Further workup revealed multiple cardioembolic strokes caused by NBTE. Extensive workup for the cause of his NBTE and subsequent cerebrovascular events revealed colorectal adenocarcinoma. Conclusion: Cryptogenic strokes in patients with cancer are cardioembolic manifestations of cancer-mediated hypercoagulability such as NBTE, which consists of sterile, platelet-fibrin vegetations on cardiac valves. The mechanism of thromboembolism in patients with cancer is based on the interaction between tumor cells and leukocytes, which creates a thrombogenic vascular lining and induces the release of substances that activate the coagulation cascade. The diagnosis of NBTE should depend on the distribution of occluded vessels, identification of thrombus, and exclusion of other possible causes such as infective endocarditis. Echocardiography is critical to diagnosing NBTE. Treatment of NBTE is poorly defined but should be directed at preventing systemic embolization and managing underlying malignancy, with long-term anticoagulation recommended by the American College of Chest Physicians. Unfractionated heparin is currently recommended to reduce rates of ischemic stroke in patients with cancer.> Disclosures: D. Babici: None. P. Phillip Johansen: None. A. Rodriguez-Hernandez: None. S. Sommerville: None. B. Snelling: None. T. D. Miller: None.